Phytochemical profiling, antioxidant, enzymatic inhibitory, and antibacterial activities of Wigandia ecuadorensis - Viteri, Rafael; Espinoza, Fernando; Cornejo, Xavier; Simirgiotis, Mario J.; Manzano, Patricia (Frontiers in Plant Science, 2024)
Wigandia ecuadoriensis, a member of the Namaceae family, is a source of metabolites and has been traditionally used as an anti-inflammatory. This work aimed to determine the total phenolic content (TPC), total flavonoid content (TFC), antioxidant effect, inhibition of α-glucosidase and cholinesterase enzymes (AChE, BChE), and antibacterial activity of the methanolic extract (ME) and subfractions of Wigandia ecuadoriensis. The findings revealed that ME and its subfractions exhibited significant antioxidant capacity, with the ethyl acetate fraction being the most active, displaying an IC50 of 17.66 µg/mL against the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical and 10.31 µg/mL against 2,2′azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS). This activity was attributed to its high total phenolic content (357.47 mg GAE/g). Furthermore, W. ecuadoriensis fractions showed marked antimicrobial properties against human pathogen strains with Minimum Bactericidal Concentration (MBC) values of 1.56-6.25 mg/mL for S. aureus, E. faecalis and E. coli. Furthermore, aqueous fraction fraction exhibited slight inhibition of acetylcholinesterase (IC50: 915.98 µg/mL) and butyrylcholinesterase (IC50: 380.42 µg/mL). Interestingly, EF showed the greatest inhibitory effect of α-glucosidase (IC50: 38.44 µg/mL) which is more potent than the control used, acarbose (IC50: 179.07 µg/mL). UHPLC-QTOF-MS analysis identified forty compounds, including phenolic acids, flavonoids, saponins, terpenes, and fatty acyls. As far as we know, this is the first study to evaluate the chemical composition and biological potential of W. ecuadoriensis. Our results provide the first evidence to the chemical knowledge of the species W. ecuadoriensis and demonstrate its bioactive potential as an interesting source of secondary metabolites with possible beneficial properties for health.